2016
DOI: 10.1002/mame.201500418
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Self‐Nucleation of Bio‐Based Poly(ethylene 2,5‐furandicarboxylate) Probed by Fast Scanning Calorimetry

Abstract: The present work focuses on the influence of nucleation processes on the crystallization of bio‐based poly(ethylene 2,5‐furandicarboxylate) (PEF). Nuclei formation has been studied by means of fast scanning calorimetry (FSC) both when cooling from the melt (nonisothermal conditions) and when annealing at either low‐ or high‐temperatures (isothermal conditions). FSC results show that nucleation on cooling can be prevented by using fast rates allowing to keep the polymer in its amorphous state; whereas cooling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…On the contrary, the melting occurs from 130 • C which means that seemingly some nucleation can develop during the isotherms. The results are in agreement with the investigation of Martino et al that demonstrated the formation of PEF crystals when exceeding annealing time of 1500 s and 3000 s at, respectively, 130 • C and 120 • C [46]. In conclusion, the static crystallisation is negligible in PEF up to 120 • C, whatever the test durations are.…”
Section: Thermal Behaviour In the Forming Rangesupporting
confidence: 92%
“…On the contrary, the melting occurs from 130 • C which means that seemingly some nucleation can develop during the isotherms. The results are in agreement with the investigation of Martino et al that demonstrated the formation of PEF crystals when exceeding annealing time of 1500 s and 3000 s at, respectively, 130 • C and 120 • C [46]. In conclusion, the static crystallisation is negligible in PEF up to 120 • C, whatever the test durations are.…”
Section: Thermal Behaviour In the Forming Rangesupporting
confidence: 92%
“…For PEF it was found that appearance of multiple melting depends on the crystallization temperature 56,68,69 . Sbirrazzuoli and coworkers have reported that the multiple melting of PEF occurs due to recrystallization during heating and not due to the different distributions of lamellar thickness of the material 70 . Figure 6a T c .…”
Section: Multiple Melting Behaviormentioning
confidence: 99%
“…On the other hand, a change in the kinetic regime of the melt crystallization is highlighted for T < 170°C which can be attributed to the appearance of the α′-form in this temperature range (Codou et al, 2014 ). Finally, in the work of Martino et al ( 2016a ) a very tiny self-nucleation temperature range between 195 and 198°C, allowing the crystallization rate of PEF to increase significantly, has been identified.…”
Section: Structure-properties Relationshipsmentioning
confidence: 97%